Manajemen Public Relations PT. Persib Bandung Bermartabat Di Twitter Dalam Mempertahankan Citra Perusahaan Klub Sepakbola Persib Bandung: Managemen public relations PT. Persib Bandung bermartabat di twitter dalam mempertahankan citra perusahaan klub sepakbola Persib Bandung - Kiki Esa Perdana (Linimasa : Jurnal Ilmu Komunikasi, 2020)
The development of football in Indonesia is very interesting, according to Permendagri number 32 of 2011 and 39 of 2012 rules since 2005, football clubs in Indonesia are required to have a professional company background, may no longer be funded by the state budget or regional finance, therefore, all major clubs in Indonesia , changing the structure of their management into a professional company seeking funding from sponsors. So this transition is pretty much a hassle for many football clubs, not a few clubs that are a little turned into professional management, but stuck in the old way. Still not practicing professional public relations management as it should, but still using government relations, PT. Persib Bandung is one of the clubs deemed successful in carrying out this transformation by turning to a professional company. In epistemology, PT. Persib Bandung with dignity already has many advantages with a supporter base that has been well established for a long time. Public relations management is just continuing their good performance.